LncRNA LINC00641 Sponges miR-497-5p to Ameliorate Neural Injury Induced by Anesthesia via Up-Regulating BDNF - Chen, Qingxia; Yan, Jingjia; Xie, Wenji; Xie, Wenqin; Li, Meijun; Ye, Yanle (Frontiers in Molecular Neuroscience, 2020)
Introduction: Ketamine, which is widely used in anesthesia, can induce cortical neurotoxicity in patients. This study aims to investigate the effects of long non-coding RNA (lncRNA) LINC00641 on the ketamine-induced neural injury. Materials and Methods: In this study, rat brain embryonic stem cell (ESC)-derived neurons were used as a cell model and Sprague–Dawley postnatal day 7 rat were used for experiments in vivo. Ketamine-induced aberrant expression levels of LINC00641, miR-497-5p and brain-derived neurotrophic factor (BDNF) were examined by qRT-PCR. The effects of LINC00641 and miR-497-5p on ketamine-induced neural injury were then examined by MTT assays and TUNEL analysis. In addition, the activity of ROS and csapase-3 was measured. The regulatory relationships between LINC00641 and miR-497-5p, miR-497-5p and BDNF were detected by dual-luciferase reporter assay, respectively. Results: Ketamine induced the apoptosis of ESC-derived neurons, accompanied with down-regulation of LINC00641 and BDNF, and up-regulation of miR-497-5p. LINC00641 overexpression enhanced the resistance to the apoptosis of ESC-derived neurons, while transfection of miR-497 -5p had opposite effects. Furthermore, LINC00641 could bind to miR-497-5p and reduce its expression, but indirectly increase the BDNF expression, which was considered as a protective factor in neural injury and activated TrkB/PI3K/Akt pathway. Conclusion: Collectively, LINC00641/miR-497-5p/BDNF axis was validated to be an important signaling pathway in modulating ketamine-induced neural injury.